Catalytic degradation of dyes using gold nanoparticles supported over chitosan coated cotton cloth composite - Awais; Fahim Ullah; Adnan Khan; Romana Khan; Sher Bahadar Khan; Khalid A Alzahrani; Nauman Ali; Mazhar Ul-Islam; Muhammad Tariq Saeed Chani; Tahseen Kamal (Materials Research Express)
The increasing environmental threat posed by various dye contaminants in wastewater necessitates the development of efficient catalytic systems for their removal. This research work investigates the synthesis of gold nanoparticles (Au NPs) on chitosan-coated cotton cloth (CH-CC) as a versatile catalyst for the reduction of hazardous dyes, specifically methylene blue (MB), rhodamine B (RB), and congo red (CR). The Au-CH-CC composite was prepared by treating CH-CC with HAuCl _4 and reducing the formed ions using sodium borohydride. XRD, SEM, and EDX were adopted as characterization techniques which confirmed the successful formation of gold nanoparticles. The catalytic performance was evaluated via UV–visible spectrophotometry, revealing rapid dye reductions of 93%, 86%, and 98% for MB, RB, and CR in 12, 9, and 6 min, respectively. Kinetic analysis indicated pseudo-first-order kinetics by using the Au-CH-CC as catalyst, with respective rate constants of 0.18, 0.23, and 0.54 min ^−1 . The recyclability of the catalyst was demonstrated by repeatedly recovering and reusing it in three successive cycles. The findings in this study reveal the potential of utilizing Au NPs on biomass-derived materials for environmentally friendly dye remediation, presenting a sustainable approach to mitigating dyes pollution from wastewater.